New Officers Of Pennsylvania Anthracite Section (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1919)
The following officers were elected by the Pennsylvania Anthracite Section of the A. I. M. E. on the evening of June 28th. Chairman, R. V. Norris; vice-chairmen, C. F. Huber, W. G. Whildin, W. J. Richards, Eli Conner; executive committee, Douglas Bunting,. W. W. Engle, Chas. Enzian, J. M. Humphrey, A. B. Jessup, R. A. Quinn; secretary and treasurer, Paul Sterling.